(untitled) ("Conference on Universal Science Research 2023", 2023)
Technological advancements have revolutionized the way English is taught and learned. The integration of digital tools and resources has provided educators with new avenues to enhance language instruction. Interactive multimedia tools, online platforms, language-learning applications, and virtual reality simulations offer engaging and immersive experiences for learners, promoting active participation and facilitating language acquisition. This article explores the impact of technology on English language education, focusing on its benefits, challenges, and potential future developments.